Complexions in WC-Co cemented carbides. (1st May 2018) - Liu, Xingwei; Song, Xiaoyan; Wang, Haibin; Liu, Xuemei; Tang, Fawei; Lu, Hao
Abstract: The studies are focused on the complexions in the WC-Co cemented carbides, which represent the phase-like interfacial state at the WC/Co interfaces. A series of experiments were designed to investigate the formation, growth and transformation behaviors of the complexions. It was found that the complexions with cubic structure can be stabilized by quenching or by dissolution of specific elements added in form of carbides as grain growth inhibitors. The characteristics and stabilization conditions of the complexions, as well as their influences on the interfacial structures and mechanical properties of the cemented carbides, were studied in detail for additions of various inhibitors such as VC, Cr3 C2, TiC, TaC and NbC. The results disclose that the existence of complexions is dominated by their formation energy and misfit at the interface between the complexion and WC. The stabilization of complexions, on one hand, inhibits WC grain growth effectively, on the other hand separates the bonding of WC and Co, thus causes decrease of the resistance against intergranular fracture of the cemented carbides. It is proposed that tailoring the stability of complexions by matching inhibitor and carbon content can lead to both the high fracture toughness and high strength of the cemented carbides. Graphical abstract: The existence of complexions is dominated by the formation energy and misfit at the interface between the complexion and WC. The stability of complexions can be tailored by matching inhibitor and carbon content, and both the high fracture toughness and high strength can be achieved by controlling complexions in the cemented carbides. Image 1